Humification of poultry waste and rice husk using additives and its application - Maryam Mushtaq; M. K. Iqbal; A. Khalid; R. A. Khan (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose The purpose of this study was to assess the efficacy of inorganic additives during the humification of poultry waste and rice husk. Methods Poultry waste mixture was treated with aluminum sulfate 3% and rock phosphate 2% during co-composting of mixture in mechanical composter and evaluated the potential of humification and compost nitrogen mineralization in incubation and pot study. Results The mesophilic to thermophilic phase of composting mixture is prolonged due to the rise in temperature, pH and ammonia that steadily decrease near the maturation phase. The humification rate (HR), humification index (HI), degree of polymerization (DP) and cation exchange capacity (CEC) increased in enriched compost as compared to unenriched with the composting process. The germination index (GI) of enriched compost (C/N:10.8) was significantly greater than unenriched compost (C/N:23.43). These all maturity indices, i.e., C/N, CE, HI, DP, HR revealed the significant correlation with each other. In the incubation study, nitrogen mineralization was also evaluated and nitrogen was applied at the rate of 50 kg-N/ha using the enriched and unenriched compost and found high mineralization in enriched compost due to low C/N. A laboratory-scale pot experiment was also conducted, applied the compost at a rate of 100 kg-N/ha and recorded the encouraging results in growth and nutrition value of Abelmoschus esculentus plant. Conclusion It was concluded that use of additives have a significant impact on humification of poultry waste.